Implementasi Pembelajaran Inovatif untuk Pemahaman dalam Belajar Fisika di SMU - Wayan Ardhana dkk Wayan Ardhana dkk (Universitas Negeri Malang, 2016)
This study aims at describing the effect of the implementation of the conceptual change instruction model as an instructional innovation and prior knowledge on remediation, understanding, and physics achievement in science. During the implementation, questionnaires and tests were administered to 336 high-school students at four schools in the cities of Singaraja and Malang. It was found that (1) prior knowledge had significant effect on the remediation and understanding, but not on learning achievement, (2) the innovative model had positive effects on remediation, understanding, and achievement, and (3) no interactive effect was found between prior knowledge and the innovative model and the remediation, understanding, and achievement in physics.